A pH-responsive organic photosensitizer specifically activated by cancer lysosomes. (September 2018) - Xue, Fengfeng; Wei, Peng; Ge, Xiaoting; Zhong, Yaping; Cao, Chunyan; Yu, Danping; Yi, Tao
Abstract: Photodynamic therapy that can cause high toxicity in cancer cells and lower toxicity in normal cells is in great demand. Herein, we report a pH-responsive photosensitizer based on BODIPY (pH-PDT ) by specific response to lysosomes of cancer cells for efficient photo dynamic therapy. The photosensitizer is highly sensitive in the pH range of 5.5–3.0, exhibiting an increased emission at 555 nm for about 12-fold. In vitro experiments confirmed that the singlet oxygen quantum yield of the photosensitizer was increased from 0.24 to 0.45 in an acidic environment (pH 5.5 to 3.5). With different pH of lysosomes in cancer cells and normal cells, thepH-PDT can specifically respond to lysosomes of cancer cell (HePG-2 cell) for photodynamic therapy of cancer and have no obvious toxicity of normal cells (HL-7702 cells). Graphical abstract: Highlights: pH-PDT is highly sensitive to pH in the range of 5.5–3.0 with increased emission at 555 nm for about 12-fold. pH-PDT shows increased singlet oxygen quantum yield from 0.24 to 0.45 when pH decreases from 5.5 and 3.5 pH-PDT locates in lysosomes of cancer cell for photodynamic therapy of cancer and have no obvious toxicity of normal cells.